Fingolimod for Irradiation-Induced Neurodegeneration - Metzdorf, Judith; Hobloss, Zaynab; Schlevogt, Sibylle; Ayzenberg, Ilya; Stahlke, Sarah; Pedreiturria, Xiomara; Haupeltshofer, Steffen; Gold, Ralf; Tönges, Lars; Kleiter, Ingo (Frontiers in Neuroscience, 2019)
Background: Cranial irradiation is a common therapy for the treatment of brain tumors, but unfortunately patients suffer from side effects, particularly cognitive impairment, caused by neurodegenerative and neuroinflammatory mechanisms. Finding a therapeutic agent protecting hippocampal neurons would be beneficial. Fingolimod (FTY720), a sphingosine-1-phosphate receptor modulator approved for multiple sclerosis, is an immunosuppressant and known to enhance proliferation and differentiation of neuronal precursor cells (NPCs). Objectives: To investigate whether pre-treatment with FTY720 protects NPCs in vitro and in vivo from irradiation-induced damage. Methods: NPCs were isolated from E13 C57BL/6 wildtype mice, treated at day 0 of differentiation with FTY720 and irradiated on day 6 with 1 Gy. NPCs were analyzed for markers of cell death (PI, Caspase 3), proliferation (Ki67), and differentiation (DCX, βIII-tubulin). Adult C57BL/6 wildtype mice were treated with FTY720 (1 mg/kg) and received a single dose of 6 Gy cranial irradiation at day 7. Using immunohistochemistry, we analyzed DCX and BrdU as markers of neurogenesis and Iba1, GFAP, and CD3 to visualize inflammation in the dentate gyrus and the subventricular zone. B6(Cg)-Tyrc-2J/J DCX-luc reporter mice were used for bioluminescence imaging to evaluate the effect of FTY720 on neurogenesis in the dentate gyrus and the spinal cord of naïve mice. Results: FTY720 protected NPCs against irradiation induced cell death in vitro. Treatment with FTY720 dose-dependently reduced the number of PI+ cells 24 and 96 h after irradiation without effecting proliferation or neuronal differentiation. In vivo treatment resulted in a significant survival of DCX+ neurons in the dentate gyrus and the subventricular zone 4 weeks after irradiation as well as a slight increase of proliferating cells. FTY720 inhibited microglia activation 24 h after X-ray exposure in the dentate gyrus, while astrocyte activation was unaffected and no lymphocyte infiltrations were found. In naïve mice, FTY720 treatment for 4 weeks had no effect on neurogenesis. Conclusions: FTY720 treatment of NPCs prior to X-ray exposure and of mice prior to cranial irradiation is neuroprotective. No effects on neurogenesis were found.